Muon-spin spectroscopy studies of hydrogen-related defects relevant to doping of diamond - Madhuku, Morgan (My University, 2009)
This study focused on investigation of the behaviour of hydrogen-related defects in diamond. Diamond represents a material with potential in electronics, particularly for high power and high temperature electronic devices operating under radiation and in corrosive environments. However, the production and characterization of high-quality diamond for electronic devices is a great challenge. The main objective is to understand the origin of structural imperfections and impurities and to reduce or control these in order to improve the electronic and optical properties of diamond. The presence of hydrogen is known to influence these properties. Therefore, very significant experimental and computational e ort is expended in trying to understand and predict the behaviour of hydrogen in diamond and in other semiconducting materials, and the recent discovery of its ability to act as a shallow dopant to enhance conductivity in some materials has generated much interest. However, most of the experimental information on hydrogen in diamond has hitherto been obtained from studies of the light hydrogen pseudo-isotope, muonium. In this thesis, we employ transverse field muon spin rotation (TF- SR) and longitudinal field muon spin relaxation (LF- SR) to investigate two specific aspects of muonium (and hence hydrogen) in diamond: Firstly, the high temperature stability of bond-centred muonium (MuBC) is investigated in a search for its possible ionization. The MuBC state in diamond is easily observed and there is a very pleasing correlation between theoretical and experimental hyperfine parameters. Curiously, despite its predicted stability, the bond-centred hydrogen (HBC) state has not yet been observed in diamond. As one proceeds with LF- SR measurements above room temperature, one encounters firstly the expected increase in the MuBC population corresponding to the well known MuT ! MuBC transition, but observed here for the first time in diamond in longitudinal field. At still higher temperatures (setting in near 1 000 K), the MuBC population decreases, a result which is consistent with MuBC ionization. There is also an indication, from the TF- SR measurements, that this is correlated with the increase in the population of the diamagnetic ( + D) species. Secondly, the muonium states in high-purity type IIa diamond grown by high-pressure and high-temperature (HPHT) synthesis are investigated in a search for the origin of the missing fraction (MF) observed in many previous muonium studies in diamond. The pure synthetic diamond gave similar fractions of the muonium states as pure natural samples. There is still a small missing fraction.